Re-animated heritage. National project Nieuwe Hollandse Waterlinie (New Dutch Water Defence Line) as a format for landscape policy (Bulletin KNOB, 2011)
Landscape policy has always been characterized, often supported but just as often hindered by its multiple origins in both landscape protection and landscape development. Along the recalcitrant and frequently inconsistent lines of preservation of monuments, nature conservation, land use, open-air recreation and the planting of new woods and shrubs respectively, landscape protection did not develop without difficulty. On a government level landscape protection was most extensively laid down in the Structure Plan for Nature Conservation and Protection of the Countryside. In this Plan the government introduced an extensive series of landscape categories, among which National Parks, National Landscapes, Valuable Agricultural Cultural Landscapes, Natural Heritage Valuable Areas, Large Landscape Unities and Valuable Scenic and/or Historical Views.In the Green Space Structure Plan from 1994 the differentiation of landscape policy was drastically reduced to the category of Valuable Cultural Landscapes and in addition a reference was made to the intended execution of large projects, such as the Randstad Green Structure and the National Ecological Network. In the revision of this Structural Plan in 2002 the category of National Landscapes was reintroduced. From the quarter of landscape development approximately every ten years a policy document is issued. The View on Landscape Creation (dating from the seventies), the View on Landscape (eighties) and the Policy Document on Landscape (nineties) are to be regarded as attempts at a synthesis of the various motives behind landscape development. The gist of these policy documents shifts from manifests for national green areas towards worked-out, integral concepts and formulas for rural-area development and closes with more and more complicatedly formulated recommendations, such as in the Development-oriented Landscape Strategy. After the Policy Document on Landscape with poorly argued maps of the so-called National Landscape Pattern, independent, development-oriented landscape policy on a national scale ceased to exist. After a period in which physical planning described landscapes in terms like 'agricultural area with high to very high cultural-historical, scientific and/or natural heritage values' respectively, these past years two policy categories have been relied on on a government level: National Landscapes and Government Buffer Zones.After the recent change of government in 2010 landscape policy as embedded in physical planning, however, seems to have evaporated forever. The Third Policy Document on Architecture 'Designing the Netherlands' from 2001 (just as the Belvedere Policy Document from 1999) is a pragmatically composed action programme in which ten concrete spatial assignments are presented. As promised in the Policy Document, these projects would have to comply with high quality standards. One of these projects was the revitalization of the Nieuwe Hollandse Waterlinie. The purpose of this project was finding a balance between consolidation, protection, utilization and adjustment of the historical qualities of this military defence structure. In the light of the analysis of a permanently groping policy for Dutch cultural landscapes, the approach to the Nieuwe Hollandse Waterlinie is an interesting reference. After all, it concerns a concrete area with historically based boundaries, with identifiable patterns and artefacts on a regional scale. The project was initiated from an interest in increase of values and is integral in tone and ambition. In the national project Nieuwe Hollandse Waterlinie cultural heritage management, landscape protection and (landscape-)architectonic quality care, region marking, recreation facilities and tourism, and water and nature policy come together. Also on the level of preservation of monuments new insights are being developed.